Usulan Penurunan Kecacatan Piston Cup Forging Menggunakan Fishbone Diagram, FMEA dan 5W+1H di Perusahaan Spare-part Kendaraan - Zahra Nursyahbani; Theodora Edita Sari; Winarno Winarno (Go-Integratif : Jurnal Teknik Sistem dan Industri, 2023)
To control product quality, companies usually limit the defect rate. If the defect exceeds the predetermined limit, then efforts are needed to improve the quality of the product. The purpose of this research is to suggest the quality improvement for one of the vehicle spare-part products in a company located in Karawang industrial area, namely Piston Cup Forging. The product has a defect rate exceeding the predetermined target. Improvement steps taken are to determine the types and factor of defects using fishbone diagram (FBD), analyze the dominant causal factors of defects using failure mode and effect analysis (FMEA), and provide proposed improvements using the 5W+1H method. Based on the results of FBD analysis, it is known that the type of gaikei minus defect is caused by four factors, namely machine, man, materials, and methods. Furthermore, based on the FMEA results, this type of the defect occurs because it is caused mostly by human factors. Therefore, in the study, it is proposed that the operator needs to re-check the machine before it is operated and evaluate the operator periodically.